Integration of thermochemical energy storage in concentrated solar power. Part 1: Energy and economic analysis/optimization. (April 2020) - Tesio, U.; Guelpa, E.; Verda, V.
Highlights: High-temperature thermochemical energy storage for Concentrated Solar Power. Comparison between power cycles for indirect integration. Complete economic analysis of Calcium-Looping with cost functions. Charging process dimensioning under transient operating conditions. Optimization of heliostat field and solar receiver sizes. Abstract: Coupling of Concentrated Solar Power and Thermo-Chemical Energy Storage is a very interesting option because of the high efficiencies attainable with a renewable source and the large variation of solar radiation. Thermo-Chemical Energy Storage based on Calcium-Looping represents a promising opportunity thanks to high operating temperature, high energy density, null thermal losses and cheap calcium oxide precursor exploitable. The large variety of suitable power blocks and the importance of their integration in the discharging process makes it necessary to perform a coherent analysis of the selected alternatives, in order to compare them and establish the most convenient integration. Many aspects must be taken into account, such as system efficiency, investment costs and layout complexity. The purposes of the present work are: the development of a methodology to simulate the entire plant operations; the synthesis of heat recovery systems for both the charging and discharging processes; the execution of an economic analysis and the development of economic optimizations for the design/dimensioning of solar side and calciner side. Between the options investigated, power blocks based on supercritical CO2 are the most convenient both in terms of global efficiency (higher than 19%) and capital investment, keeping this advantage also for higher plant sizes. The methodology here developed and the results obtained are useful information for a deeper analysis of the most promising integration alternative, which is performed in the second part of this study.